Developmental Trends in False Memory Across Adolescence and Young Adulthood: A Comparison of DRM and Memory Conformity Paradigms. Issue 3 (14th February 2015) - McGuire, Katherine; London, Kamala; Wright, Daniel B.
Summary Little is known about the reliability of eyewitness memory among adolescents as most memory research has focused primarily on adults and young children. A number of studies recently have emerged outlining conditions where memory suggestibility increases from early childhood to adulthood. These developmental reversals are found in semantic association tasks such as the Deese–Roediger–McDermott (DRM) paradigm and have not yet been thoroughly investigated among adolescents. In the current study, we examined DRM performance among 11–21 year olds (N = 245). Extending the work comparing children and adults, false memory on the DRM task increased with age. False memory on the DRM task was not associated with false memory on a memory conformity task. The different memory processes involved with the tasks and the implications for legal psychology are discussed. Copyright © 2015 John Wiley & Sons, Ltd.